Management of chronic Achilles tendon tear by reverse gastrocnemius turndown flap and augmentation with FHL tendon – A case series - Devarshi Rastogi; Mayank Mahindra; Shah Wali Ullah; Sanjiv Kumar; Shitanshu Kumar Singh (Asian Journal of Medical Sciences, 2022)
Background: Chronic Achilles tendon ruptures are defined as tears that occur 4–6 weeks after injury and also those that fail to heal at 6–12 weeks. Reduced plantar flexion, discomfort, trouble walking, chronic pain, poor wound healing, and rerupture are all problems of chronic tears. The V-Y flap, turndown flap, peroneus tendon graft, flexor digitorum graft, and flexor hallucis longus (FHL) graft are just a few of the operations proposed and claimed to have great post-operative clinical results. Aims and Objectives: This study aims to evaluate the functional outcome of tendon debridement, gastrocnemius turndown flap, and augmentation with FHL tendon to reconstruct a chronic Achilles tendon tear. Materials and Methods: This study included 12 patients with chronic Achilles tendon rupture. The gastrocnemius turndown flap, which was augmented with FHL tendon, was used to treat all of the patients in the study. The American Orthopaedic Foot and Ankle Society (AOFAS) score, Achilles Tendon Total Rupture Score (ATRS) score, and ability to do repetitive single affected side heel raises were the outcomes evaluated in this study. Results: After a year of follow-up, the mean AOFAS score increased from 61.17 points preoperatively to 86.67 points. The mean ATRS improved significantly from 41.91 points preoperatively to 84.41 points at the most recent follow-up (P<0.05). One of the patients developed a superficial wound infection, treated with wound debridement, and antibiotics. One year after surgery, all patients could do single-leg heel raises. There was no sign of rerupture. Conclusion: Reverse gastrocnemius turndown flap with FHL tendon is a well-tolerated and effective treatment of chronic TA rupture.